Kualitas Dadih Kacang Hijau dan Susu Sapi dengan Penambahan Sari Jeruk Manis dan Mangga Kweni - Fiyana, Siti Nur Ari, Titik Suryani, M.Sc (2016)
The curd was a traditional cheese product it was a typical of West Sumatra which made from buffalo milk that fermented in bamboo tubes for 48 hours. The curd contained LAB (Lactic Acid Bacteria) potential as probiotics. This study used a formulation of mung bean juice and cow's milk instead of buffalo milk. The aim of the study was to know quality curd mung bean and cow's milk with the addition of sweet orange and kweni mango. The research method used a completely randomized design (CRD) with a factor, such as: type of fruit: Control (JK0), Sweet Oranges in 22ml (JK1), 24ml (JK2), and 26ml (JK3), Mango Kwenies in 22 ml (JK4), 24 ml (JK5), and 26 ml (JK6). The results showed the highest protein levels in treatment JK1 6 g/l, the lowest protein level in treatment JK0 4.1 g/l. the highest calcium level in the treatment JK2 8.86 g/l, and the lowest calcium levels in treatment JK4 4.08 g/l. The most dominant curd product was yellowish white color, distinctive smell of cow's milk, the taste was quite savory and sour, the tecture was soft and chewy, the dominant received panelists were JK6 treatment.